Immunological recovery with BIC/FTC/TAF: CD4 T-cell count and CD4/CD8 ratio as markers of response - Bono, Valeria; Marchetti, Giulia C (The New microbiologica, 2025)
The CD4/CD8 ratio is a crucial marker of immune dysregulation, immune senescence, and inflammation, predicting outcomes such as non-AIDS conditions and mortality. A low CD4/CD8 ratio is common in late HIV diagnoses, which remain frequent in Italy, where 58% of new cases occur with advanced immune suppression (CD4 <350 cells/μL). Recent advancements in cART, particularly bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF), have demonstrated superior efficacy in restoring immune function, especially in late-stage HIV. BIC/FTC/TAF offers high virological suppression, durable immune reconstitution, and a favorable safety profile. Comparative studies highlight its advantages in improving CD4 counts, reducing HIV RNA, and mitigating inflammatory markers, suggesting potential cardiovascular benefits. These findings position BIC/FTC/TAF as an effective option for advanced HIV treatment, contributing to better immune recovery and reduced systemic inflammation.